Research on Data Cleaning in Data Mining - Zhang, Xiangfei (Journal of Theory and Practice of Engineering Science, 2025)
In simple terms, data mining is to integrate all of the data, to find and integrate, in learning, pattern recognition, therefore, we will learn all kinds of subjects, for example, statistics, management, database, etc., therefore, in contemporary society in the development of data mining technology is also more and more quickly, also more and more people like to use to integrate data mining and data warehouse technology, Once found that can use these data in the process of data mining, the value of the data warehouse technology will replace the data integration, data cleaning is to organize the error data or dirty data, therefore in the process of data mining must be combined with the data cleansing can let the data in the database to ensure the authenticity and validity. Therefore, in the development of data mining in China, there should be a lot of learning and improvement content, China should continue to establish and improve the data mining and data cleaning strategy research.